PENDIDIKAN AKHLAK DALAM BINGKAI KEARIFAN LOKAL - Andika Hariyanto Surbakti (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2021)
The teachings of Islam that synergize with the values ​​of local wisdom of the community will form a nation generation that advances Islamic civilization and is in accordance with the nation's character. These values ​​must be instilled in every human soul and continue to be instilled from one generation to the next. The purpose of this paper is to elevate the local wisdom education system to the Gayo community in providing moral education for each member of the community. The Gayo community has long implanted regulations and customs that show a moral education system for their community. Some of them are reflected in the Marriage system, the Inheritance System, Mutual Cooperation and Declining Mani. According to the analysis of the writer the cultural system carried out has moral education values ​​which are very important to be preserved and developed. Moral education contained in these customs is a forerunner to form an environment that is aware of the importance of moral education and culture.